First-principles calculations of electronic properties, surface stability and photocatalytic potentials of seleno-germanates A2GeSe4 (A = Mg; γ-Sr) surfaces for a promising visible light photocatalytic application. (March 2021) - Barde, Abdu; Joubert, Daniel P.
Abstract: The four low-index, (100), (101), (110) and (111) surfaces of the A 2 GeSe 4 (A = Mg; γ -Sr) seleno-germanates were studied using the first principles generalised gradient density functional theory approximation. From the optimized surfaces structures, surface stabilities were established by calculating the surface energies. Our calculation reveals that the Mg 2 GeSe 4 (101) and γ -Sr 2 GeSe 4 (111) surfaces are the most energetically stable surfaces, for the two compounds, respectively. On the Mg 2 GeSe 4 (101) and γ -Sr 2 GeSe 4 (111) most stable surface, the electronic properties, charge density, electrostatic potential, work function, band gap center and band-edge potentials were calculated. Calculated electronic density of state reveal for Mg 2 GeSe 4 (101) a metallic and γ -Sr 2 GeSe 4 (111) a semiconductor surface. Analysis of total and partial density of state of surface compared to bulk reveals conduction band shifting toward valence band and exhibit surface electronic density state corresponding to p -orbital of Se atom contribution around the Fermi-energy. Bader charge density analysis of the Mg 2 GeSe 4 (101) and γ -Sr 2 GeSe 4 (111) surfaces reveals charge depletion around Mg, Sr and Ge atoms and charge accumulation around the Se atoms, which indicate covalent bonding between the Se and Ge, Mg and Sr atoms. The stable surfaces were used to calculate the electrostatic potential and thus determine the work function, band gap centre and band edges. The band edges compared to redox potential of water show that Mg 2 GeSe 4 (101) and γ -Sr 2 GeSe 4 (111) surfaces suggest that are promising visible light photocatalytic materials